Water quality in the basin the Rimac river, sector of san mateo, affected by mining activities - Calla LLontop, Helen (2010)
This research approaches the effects that the water quality of Rimac river has presented opposite to the development of the mining activity in San Mateo’s district of Huanchor located in Huarochirí’s province in Lima. The area of study is a zone where the mining polymetallic activity has developed from many decades behind approximately from the 30s, epoch in which there had not the current requirements of the environmental legal regulation and for such motive we have nowadays catalogued in the zone 21 environmental mining liabilities between mine entrance, tailing ponds and infrastructures seated on the banks of the Rimac water and of it’s principal tributaries like Blanco and Aruri rivers which nowadays are important sources of lixiviados to Rímac river water, due to the fact that they aren`t being handled by the private company and for the State. The quality water investigation has been developed in a series of time of ten years taking as bosses of analysis to the metallic ions; which have had a comparative analysis with the national and international legal environmental regulations such as the Standards of the World Health Organization, the Standards of Canada for Water of Irrigation, the General Law of Waters and the National Standards of Quality of the Water (ECAS) for the Category III passes by the Supreme Decree N.° 002-2008-MINAM, being the above mentioned the legal environmental decisive modal for the analysis of the quality of the water of the year 2008, since they constitute the ideal values that assure the quality of the water superficial resources of the country. We obtained from the analysis that the Cadmium, Lead, Manganese, Arsenic and Iron were the elements that had to receive a corrective treatment since their concentrations in Rimac water were bigger than the established in the standards of water quality. After obtaining these results the source was selected the source to treat and there chose as case of study the effluent end of Mining Company San Juan S.A, for being the mining company with major historical path in the zone and the one that has major capacity of production in San Mateo’s district; likewise because was observed that there was a major increase in the concentrations of the metallic ions in the Rimac water after receiving the final vertimento of the mentioned company, in comparison with other points of sampling that were presenting minor concentrations; for which had presented a technical economic offer based on the application of the technology HDS –Muds of high density for the treatment of the effluent end of Mining company San Juan for being the best technology used in the whole world for the treatment of effluent miners with content of lead, cadmium, arsenic, manganese and iron, and because it presents a level of efficiency that it allows to obtain effluent with the minimal concentrations of metals allowing that it`s unload to the body recipient should not cause any adverse effect in the components of the ecosystem, allowing to expire this way with the standards fixed by the current requirements of the environmental regulation. Then we had an objective to reduce the concentrations of the metallic elements in the Rimac water of San Mateo’s district and improve the current system of treatment of effluent miners of Mining Company San Juan, putting into practice a technology that offers the highest standards of environmental quality; benefiting this way the ecological balance and the quality of the waters Rimac river.